The impact of psychological capital on the job satisfaction of medical staff: an empirical study - Chen Chong (2017)
As the reform of the health care system deepens and the competition in the medical sector becomes increasingly fierce, medical staff are faced with more pressure and challenges. As a result, they need strong intrinsic motivation to cope. Besides, medical staff’s job satisfaction is closely linked to the performance of themselves and even that of the entire organisation, so hospital managers also need to raise the job satisfaction of their staff. Existing research on psychological capital (PsyCap) demonstrates that it brings returns to the organisation. The study on the PsyCap of medical staff has added a new path to the Human Resources Management of hospitals and provided a novel perspective in the management and training of medical staff. Thus it is meaningful to carry out a combined research on the PsyCap of medical staff and their job satisfaction. This study first explores the dimensions of PsyCap of medical staff in China and develops a scale for its measurement, and then the mechanism through which PsyCap influences job satisfaction is investigated. Based on a standard scale development process (in-depth interviews, open-ended questionnaire, reliability and validity evaluation with exploratory and confirmatory factor analyses), finally a two-dimensional and nine-subdimensional 39-item measurement scale for PsyCap was validated. The theoretical model was applied to a sample of 400 doctors, nurses and medical technicians from 11 AAA-hospitals in Hangzhou, China, and estimated with Structural Equation Modelling. Results revealed that Interpersonal PsyCap and Task-based PsyCap influence Job Satisfaction through Work Motivation and Organisational Commitment, but the indirect effect of Interpersonal PsyCap is stronger than that of Task-based PsyCap. Theoretical and managerial implications are proposed based on these results.